Kant’s conception of race and modern political science - Salikov, Alexey (Con-Textos Kantianos. International Journal of Philosophy, 2024)
Racial issues remained for a long time one of the marginal topics in political thought. However, in the last few decades racial questions have become a topic of discussion in political science. Modern debates about race in political science are quite multifaceted and concern both practical and theoretical issues. In this regard, participants in discussions often turn to the of thinkers of the past. Much of this research focuses on the specific issue of Kant’s concept of race, which is often used as a pretext to label Kant as a ‘racist’ thinker. Why is it that Kant’s concept of race has become so important for contemporary discussions of race in political science? Could the characterizing of Kant as a ‘racist’ have a negative impact on the perception of his political philosophy? Answering these questions is the purpose of this paper.